Lettere Alle Tre Amiche. - Slataper, Scipio. (Alpe Adria e Dintorni, Itinerari Mediterranei Ser., 2022)
The volumes published in this series analyze literary and cinematic narrations from the Alpe Adria region and the Mediterranean. The literary, visual, historical, cultural, and inguistic dynamics which characterize these areas play an essential, multifaceted role in their various manifestations, past and present. Against this backdrop, the term "border" becomes a highly complex, volatile concept.